Management changes resulting from hospital accreditation - João Lucas Campos de Oliveira; Carmen Silvia Gabriel; Hosanna Pattrig Fertonani; Laura Misue Matsuda
ABSTRACT Objective: to analyze managers and professionals' perceptions on the changes in hospital management deriving from accreditation. Method: descriptive study with qualitative approach. The participants were five hospital quality managers and 91 other professionals from a wide range of professional categories, hierarchical levels and activity areas at four hospitals in the South of Brazil certified at different levels in the Brazilian accreditation system. They answered the question "Tell me about the management of this hospital before and after the Accreditation". The data were recorded, fully transcribed and transported to the software ATLAS.ti, version 7.1 for access and management. Then, thematic content analysis was applied within the reference framework of Avedis Donabedian's Evaluation in Health. Results: one large family was apprehended, called "Management Changes Resulting from the Accreditation: perspectives of managers and professionals" and five codes, related to the management changes in the operational, structural, financial and cost; top hospital management and quality management domains. Conclusion: the management changes in the hospital organizations resulting from the Accreditation were broad, multifaceted and in line with the improvements of the service quality.